Call me sister! - Révauger, Cécile (2020)
This article focuses on terminology and the importance of avoiding gendered discrimination in freemasonry. To address contemporary issues, we shall provide an historical context. For instance, the use of "sister" rather than "brother" in French lodges is still controversial. This can be related to the debate within the French Academy about the feminization of job titles. Although the historical and linguistic context is different for the mixed and feminine orders in France, the United Kingdom and the USA, there are some similitudes as far as gender is concerned.